2007
DOI: 10.1097/wno.0b013e3180334cb0
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Motor Disorders in Mitochondrial Encephalopathy With Lactic Acid and Stroke-Like Episodes With the 3271 (T-C) Point Mutation in Mitochondrial DNA

Abstract: On the basis of eye movement recordings, patients with MELAS have frontal cortex as well as cerebellar dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Iwasaki et al suggested a relationship with the vestibular dysfunction of the mitochondrial A3243G mutation [6] . In addition, there are only reports from Shinmei et al [7] and Choi et al [8] for eye movement abnormality; thus, our report is the first one describing ENG. Shidara et al [9] explained that there is less vestibular damage compared to hearing impairment because it is resistant to an ischemic condition or is anatomically likely to obtain blood flow from the collateral circulation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Iwasaki et al suggested a relationship with the vestibular dysfunction of the mitochondrial A3243G mutation [6] . In addition, there are only reports from Shinmei et al [7] and Choi et al [8] for eye movement abnormality; thus, our report is the first one describing ENG. Shidara et al [9] explained that there is less vestibular damage compared to hearing impairment because it is resistant to an ischemic condition or is anatomically likely to obtain blood flow from the collateral circulation.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, an ETT in ENG revealed a saccadic pattern, which is said to be exhibited by the brainstem/cerebellar single lobe disorder, and OKN showed a decrease in nystagmus velocity caused by a brainstem lesion [10] . With regard to the caloric test, in previous reports, there were various findings, and bilateral nonresponsive cases were also observed, but an apparent caloric response was seen in this case [7] . Therefore, at the least, the neural transmission and function remained via the lateral semicircular canals, superior vestibular nerves, and vestibular nuclei.…”
Section: Discussionmentioning
confidence: 93%
“…Shinmei et al (11) described persistent ocular motor dysfunction (including downbeat nystagmus, square wave jerks, impaired SP, and hypermetric and hypometric saccades) in patients with MELAS and normal MRI. Shinmei et al (11) described persistent ocular motor dysfunction (including downbeat nystagmus, square wave jerks, impaired SP, and hypermetric and hypometric saccades) in patients with MELAS and normal MRI.…”
Section: Discussionmentioning
confidence: 99%
“…However, at least 29 mitochondrial DNA (mtDNA) mutations and at least 7 mitochondrial transfer RNA gene mutations have been identified in the disorder. 1,6,8 Step Description 1a…”
Section: Mitochondrial Dna Mutationsmentioning
confidence: 99%